The Investigative of Satisfaction Levels on Marketing Strategy PT Fast Food Indonesia TBK in KFC Central Balikpapan Branch - Adi Hermawansyah; Budi Eko Soetjipto (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
In this the objective of research this research is to determine the Influence of Product, Promotion and Price on Customer Satisfaction on PT. Fast Food Indonesia TBK Products. (KFC) Central Balikpapan. Type study Which used is quantitative research. The number of samples in this study was 310 customers who ate various kinds of fast food products at KFC Central Balikpapan for 1 month. The sampling technique used in this study was probability sampling. Analysis data Which used is a regression linear multiple. The test tools used are instrument tests, classical assumption tests, and hypothesis tests. The results which is obtained illustrates that in the variable Product, Promotion, And Price own direction connection Which positive and has a significant influence on Customer Satisfaction and Products have a dominant influence on Customer Satisfaction, whereas